Avaliação mecânica de argamassas de revestimento com adição de microcelulose cristalina sob ação de ciclos de choque térmico - Kachuba, Thamiris Guimarães (2025)
Rendering mortars are constantly exposed to temperature variations, alternating between heat and cold, sun and rain, which generate thermal shock cycles that can compromise their durability. In this context, this study evaluated the impact of incorporating microcrystalline cellulose (MCC) on the performance and durability of these mortars, with an emphasis on resistance to thermal shock cycles. In the methodology, the mortars were evaluated in the fresh state through tests for incorporated air content, bulk density, and consistency index using the flow table test. After curing, they were subjected to wetting and drying cycles, simulating the effect of thermal shock, and assessed for compressive strength and flexural tensile strength. The results indicated that MCC increased the mixture's density in the fresh state. In terms of mechanical performance, the formulations exhibited behavior like the reference. The MCC additions in the rendering mortars did not positively influence flexural tensile strength properties. Thermal shock significantly affected compressive strength. However, flexural tensile strength was not significantly influenced by the tested additions after thermal shock cycles. Thus, it can be concluded that while the incorporation of MCC increased the mixture's density in the fresh state, it also led to greater vulnerability to thermal shock.